2011
DOI: 10.1258/jtt.2011.101208
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of benefit from telerehabilitation in routine care: a systematic review

Abstract: We systematically reviewed the evidence on the effectiveness of telerehabilitation (TR) applications. The review included reports on rehabilitation for any disability, other than mental health conditions, and drug or alcohol addiction. All forms of telecommunications technology for TR and all types of study design were considered. Study quality was assessed using an approach that considered both study performance and study design. Judgements were made on whether each TR application had been successful, whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
107
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 70 publications
(31 reference statements)
3
107
0
12
Order By: Relevance
“…Second, a broad connectivity coverage is needed to reach most users at home. To date, reviews of the scientific literature on telerehabilitation are qualitative syntheses mainly addressing issues related to neurological rehabilitation [11][12][13][14] . Recently, Laver and colleagues published the first systematic review with meta-analysis of telerehabilitation services for stroke 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, a broad connectivity coverage is needed to reach most users at home. To date, reviews of the scientific literature on telerehabilitation are qualitative syntheses mainly addressing issues related to neurological rehabilitation [11][12][13][14] . Recently, Laver and colleagues published the first systematic review with meta-analysis of telerehabilitation services for stroke 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In the area of physiotherapy, the use of telemonitoring technologies has been proposed as an alternative for providing affordable functional rehabilitation services and reducing hospital overloads, thus removing some space-time constraints [8], [9]. A retrospective study with 155 patients and 155 control subjects shown that the costs of hospital bed days of care (1,449 days) in the year before the implementation of telerehabilitation programs totaled approximately $1,500,000, which decreased more than around $804,000 the year following the implementation of the telerehabilitation program, which represents a 46% decrease in costs and a decrease of 826 days of care [10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the charges depend on the cost of living in each country, a fact that makes more difficult to estimate constant economic benefits of telerehabilitation. Therefore, the cost effectiveness of telerehabilitation programs has been evaluated for a specific disability, as described in [8]- [10], [12]. Thus, telerehabilitation is still considered a growing alternative to traditional face-to-face therapy that employs technological solutions to remotely provide rehabilitation care in both clinical centers and in-home programs.…”
Section: Introductionmentioning
confidence: 99%
“…A definition of success for a telemedicine application is that it performs as well as a similar alternative intervention, or better than the alternative if the telemedicine option includes additional services. 16 In the study by Ishani et al details were not available on services provided by usual care so that the success of their initiative is not entirely clear. If the intervention was more elaborate, economic analysis would be required to inform clinical and policy decisions.…”
mentioning
confidence: 99%